The Impact Of Covid-19 On Stock Price And Stock Trade Volume (Case Study of Food and Beverages Companies Listed on the Indonesia Stock Exchange) - Latifatus Sholikhah; Novi Darmayanti; Have Zulkarnaen (Future Science, 2023)
The first Covid-19 case in Indonesia was announced on March 2 2020. This study aims to find out whether there is a significant difference in stock prices and stock trading before and after Covid-19 entered Indonesia (Case Study of Registered Food and Beverages Companies on the Indonesian Stock Exchange). The data for this study were taken 9 months before and 9 months after Covid-19 in Indonesia. Data were processed by paired sample t-test, using SPSS. From the results of the data processing, it shows that there was a significant difference in stock prices before and after the announcement of the first case of Covid-19 in Indonesia. This is indicated by a significance value of 0.011 <0.05. Where stock prices have decreased compared to before the Covid-19 case. Meanwhile, stock trading volume also shows a significant difference. Where the significance value is 0.003 <0.05. The stock trading volume after the announcement showed an increasing value.